Pengaruh Up Grade Transformator 160 kVA dan 100 kVA Menjadi 250kVA/400V Terhadap Biaya Operasional Pemakaian Energi Listrik di Hotel Tonys Villa Resort and Spa - I Wayan Sutama; Komang Hermawan; I Wayan Suriana (Jurnal Ilmiah Telsinas, 2022)
Hotel Tonys Villa and Resort was established in 2000 which is one of the 4-star hotels on the island of Bali which is located on Jalan Petitenget, South Kuta District, Badung. This hotel has a number of rooms, namely 22 Bungalow Rooms, 9 Pinky Villas, 40 Hotel Rooms, 3 large public pools and so on. One of the problems faced by this hotel is the increase in energy operational costs that are paid more than the budget with a minus average of Rp. 837,713 to Rp. 11,851,463 for each month. The method used is to analyze electricity cost savings by upgrading 160 and 100 KVA transformers to 1 250 KVA transformer, and analyze whether one 250 kVA transformer is able to carry the entire burden of Tonys Villa and Resort Hotel. The use of a 250 KVA transformer is considered more efficient than the use of a transformer (160 KVA and 100 KVA) with a cost difference of IDR 12,875,350 for each month and can save around IDR 154,504,200 within 1 year. In calculating the RM (Minimum Account) fee for the use of a 250 KVA transformer, it is considered more efficient and can save costs of Rp. 4,625,480 for each month if the use of the transformer is less than 40 hours and if the customer uses the transformer for more than 40 hours of use, then the financing will be calculated normally.